A silicate-based microwave dielectric ceramic and its preparation method and application
By adding SrTiO3 to Mg2SiO4 ceramics and adjusting its resonant frequency temperature coefficient, the temperature stability and dielectric loss problems of silicate-based microwave ceramic materials in the microwave communication field are solved, and ceramic materials with high thermal expansion coefficient, low dielectric constant and dielectric loss are achieved, which are suitable for communication substrate materials.
Patent Information
- Application Number
- CN202310489098.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-04
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2043-05-04
AI Technical Summary
The application of existing silicate-based microwave ceramic materials in the field of microwave communication is limited by mismatch in thermal expansion coefficient, poor temperature stability and large dielectric loss.
By adding a small amount of SrTiO3 to Mg2SiO4 ceramics, the resonance frequency temperature coefficient is adjusted to obtain a silicate-based microwave dielectric ceramic with high thermal expansion coefficient, low dielectric constant and dielectric loss.
The temperature stability of silicate-based microwave dielectric ceramics is improved, the thermal expansion coefficient matches other materials, and the dielectric loss is reduced. It is suitable for communication substrate materials and reduces signal transmission delay time.
Smart Images

Figure CN116535202B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of microwave dielectric ceramics, and in particular relates to a silicate-based microwave dielectric ceramic and a preparation method and application thereof. Background Art
[0002] As microwave communication technology gradually moves towards millimeter wave communication, electronic components need to maintain efficient and high-quality signal transmission capabilities and reliable working stability in high-frequency bands, which requires microwave dielectric ceramics to have extremely low dielectric constants, low dielectric losses, near-zero resonant frequency temperature coefficients, and matching thermal expansion coefficients. Generally, the signal transmission delay time is closely related to the dielectric constant. The use of low dielectric constant and low dielectric loss microwave dielectric ceramics can reduce the dielectric loss generated by electronic components during operation, reduce signal transmission delay time, and improve signal transmission efficiency. On the other hand, in order to avoid thermal stress caused by mismatched thermal expansion coefficients during operation of electronic components, which affects the service life of electronic components, microwave ceramic materials that match the thermal expansion coefficients of other materials should be used to meet the needs of substrate packaging materials for high thermal expansion coefficient microwave ceramic materials in different actual situations. Silicate microwave ceramics are a dielectric material system with low dielectric constant and low dielectric loss that has good application prospects. Among them, the Mg2SiO4 ceramic material system has a high thermal expansion coefficient, low dielectric constant and dielectric loss (ε r =6.8; Q×f=270,000GHz; τ f =-67ppm / ℃; CTE = 11×10 -6 / ℃). However, the negative value of its resonant frequency temperature coefficient is too large and its temperature stability is poor, which greatly limits its practical application in the field of microwave communication. Summary of the invention
[0003] In view of the shortcomings of the prior art, the first object of the present invention is to provide a silicate-based microwave dielectric ceramic with high relative density, good temperature stability, high thermal expansion coefficient, low dielectric constant and dielectric loss.
[0004] The second object of the present invention is to provide a method for preparing silicate-based microwave dielectric ceramics. The preparation method provided by the present invention has a simple and controllable process.
[0005] The third object of the present invention is to provide an application of a silicate-based microwave dielectric ceramic. Applying the silicate-based microwave dielectric ceramic to communication substrate materials can reduce signal transmission delay time to a certain extent, improve temperature stability, and reduce the failure of microwave components in the substrate caused by the mismatch of thermal expansion coefficients of different materials.
[0006] In order to achieve the above object, the present invention adopts the following technical solution:
[0007] The invention provides a silicate-based microwave dielectric ceramic, wherein the chemical expression of the silicate-based microwave dielectric ceramic is Mg2SiO4-xwt.%SrTiO3, wherein 2≤x≤8.
[0008] The inventors found that Mg2SiO4 ceramics have a higher thermal expansion coefficient, lower dielectric constant and dielectric loss. By simply adding a small amount of SrTiO3 to adjust the resonant frequency temperature coefficient, a silicate-based microwave dielectric ceramic with a high thermal expansion coefficient, low dielectric constant and low dielectric loss with good temperature stability can be obtained.
[0009] In the actual exploration process, the inventors tried a large number of materials with positive resonant frequency temperature coefficients, such as TiO2, CaTiO3, Ca 0.9 Sr 0.1 TiO3 is used to adjust the performance of Mg2SiO4, and it is found that only the addition of SrTiO3 can ensure that the final silicate-based microwave dielectric ceramics have both high thermal expansion coefficient, low dielectric constant and dielectric loss.
[0010] The present invention also provides a method for preparing a silicate-based microwave dielectric ceramic, comprising mixing Mg2SiO4 powder and SrTiO3 powder prepared in a designed ratio to obtain a ceramic mixed powder, then adding a binder and a lubricant to the ceramic mixed powder, and then ball milling to obtain a ball mill material, and then pressing and molding the granules obtained by granulating the ball mill material to obtain a green body, and sintering the green body to obtain a silicate-based microwave dielectric ceramic, wherein the sintering temperature is 1150°C to 1300°C.
[0011] The inventor unexpectedly discovered that the added SrTiO3 powder can, on the one hand, adjust the resonant frequency temperature coefficient of the silicate-based microwave dielectric ceramic, and on the other hand, the SrTiO3 powder can also promote the sintering of the ceramic, so that the silicate-based microwave dielectric ceramic of the present invention can be sintered and compacted at a lower temperature. Therefore, in the present invention, it is crucial to use SrTiO3 powder to adjust the resonant frequency temperature coefficient. If other titanium-containing oxides are used, sintering at a higher temperature is required, which will lead to the formation of other phases and thus the performance cannot be maintained.
[0012] According to a preferred embodiment, the process for obtaining the Mg2SiO4 powder is as follows: MgO powder and SiO2 powder are mixed to obtain a mixed powder, the mixed powder is wet-milled to obtain a ball-milled powder, and the ball-milled powder is pre-calcined to obtain the Mg2SiO4 powder.
[0013] Further preferably, the purity of the MgO powder and SiO2 powder is ≥99.99%.
[0014] Further preferably, in the mixed powder, the mass ratio of MgO:SiO2=2-6:1-5.
[0015] Further preferably, during the wet mixing ball milling, anhydrous ethanol is used as the ball milling medium, ZrO2 balls are used as grinding balls, the rotation speed of the wet mixing ball mill is 300-450 r / min, and the wet mixing ball milling time is 18-24 h.
[0016] The inventors found that in the preparation process of Mg2SiO4 powder, the mixed powder is wet-milled, and the rotation speed and time of the wet-milling are controlled within the scope of the present invention, and the performance of the silicate-based microwave dielectric ceramic finally obtained is optimal.
[0017] More preferably, during the wet ball milling, the ZrO2 balls are composed of large balls with a diameter of 6 to 10 mm and small balls with a diameter of 2 to 6 mm, wherein the mass ratio of the large balls, the small balls and the mixed powder is 3 to 5:1 to 2:1 to 2.
[0018] During wet mixing ball milling, controlling the grinding balls and the ball milling ratio within the above range can further improve the performance of the final ceramic material.
[0019] In actual operation, the material obtained after wet-mixed ball milling is dried to obtain ball-milled powder.
[0020] Further preferably, during the pre-firing, the heating rate is 1-5°C / min, the pre-firing temperature is 1000°C-1300°C, and the pre-firing time is 2-4h.
[0021] Preferably, the purity of the SrTiO3 powder is ≥99.9%.
[0022] In a preferred embodiment, the binder is PVA and the lubricant is stearic acid, wherein the amount of PVA added is 2wt.% to 5wt.% of the mass of the ceramic mixed powder, and the amount of stearic acid added is 1wt.% to 5wt.% of the mass of the ceramic mixed powder.
[0023] The inventors found that the microwave dielectric ceramics obtained by adding a binder, a lubricant and a ceramic mixed powder to ball-mill and finally sintering have the best performance.
[0024] In a preferred embodiment, during the ball milling, anhydrous ethanol is used as the ball milling medium, the ball-to-material ratio is 5 to 10:1, the ball milling speed is 300 to 450 r / min, and the ball milling time is 8 to 12 h.
[0025] Through ball milling, on the one hand, the two raw materials can be mixed more evenly, and on the other hand, the particle size of the raw materials can be further reduced to promote sintering.
[0026] In a preferred embodiment, the compression molding pressure is 2-5 MPa, and the pressure holding time is 3-8 min.
[0027] The inventors have found that by controlling the pressing pressure within the above range, all silicate-based microwave dielectric ceramics will eventually have the highest relative density and the best dielectric properties.
[0028] In a preferred embodiment, the sintering temperature is 1150° C. to 1300° C., the holding time is 3 to 5 hours, and the heating rate is 1 to 5° C. / min.
[0029] The present invention also provides application of the silicate-based microwave dielectric ceramic, and the silicate-based microwave dielectric ceramic is applied to substrate materials of microwave components.
[0030] Beneficial effects of the present invention:
[0031] The present invention is aimed at the current situation in the prior art that microwave dielectric ceramics are greatly limited in their use due to mismatched thermal expansion coefficients, poor temperature stability and large dielectric loss. The present invention obtains microwave dielectric ceramics with a high thermal expansion coefficient, high relative density, low dielectric constant and dielectric loss by sintering a system composed of metal oxides and non-metallic oxides at 1150°C to 1300°C. The preparation method of the present invention is simple, and the obtained microwave dielectric ceramics can better match the thermal expansion coefficients of other substrate materials, and the obtained material is a material that can be used for communication substrate materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a process flow chart of Example 1 of the present invention.
[0033] Figure 2 This is the XRD spectrum of the Mg2SiO4-xwt.%SrTiO3 (2≤x≤8) ceramic prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0034] The present invention is further described below. The following examples are only used to more clearly illustrate the technical solution of the present invention, and are not intended to limit the protection scope of the present invention.
[0035] The density and microwave dielectric properties of the present invention are tested by the following methods:
[0036] (1) Archimedes drainage method for density measurement
[0037] The sample was measured after preparation. This experiment used the Archimedes drainage method to measure the density of the sample. Because the thickness and width of the sample are not absolutely consistent, there will be a large error if the density is obtained by dividing the mass by the volume. First, use an electronic balance to weigh the mass of the sample in the air as G1, and suspend the sample in water without contacting the bottom of the beaker filled with water placed on the balance. The buoyancy in the water is measured as g1, and the obtained density is calculated by the following formula:
[0038]
[0039] (2) Testing of microwave dielectric properties
[0040] The dielectric properties of microwave dielectric ceramics are mainly dielectric constant (ε r ), quality factor (Q×f) and resonant frequency temperature coefficient (τ f ). The dielectric resonator method proposed by Hakki-Coleman, namely the parallel plate resonance method, is used to measure the dielectric constant and quality factor.
[0041] The principle of the dielectric resonator method is to place a cylindrical microwave dielectric ceramic sample in the center between two infinitely large and parallel conductive metal plates to form a semi-closed transmission resonator. During the test, two probe-type coupling antennas are inserted on both sides of the resonator sample. A microwave signal is derived from a probe-type coupling antenna and input into a microwave network analyzer. The network analyzer calibrates the resonant frequency and the resonant line width at both ends of the resonant cavity. In this way, a series of resonant frequencies can be measured with a microwave dielectric network analyzer, and then the dielectric constant and quality factor of the microwave material can be calculated.
[0042] Comparative Example 1
[0043] Step 1: Calculate and weigh the corresponding mass of MgO and SiO2 raw material powders (purity of 99.99%) according to the chemical formula ratio. Place the accurately weighed powders in a ball mill for ball milling. During the wet mixing ball milling process, anhydrous ethanol is used as the ball milling medium. ZrO2 grinding balls with diameters of 8 mm and 4 mm are added. The total mass ratio of large and small grinding balls to powder is 2:1:1. Stir thoroughly with a glass rod to mix them evenly. Place them in a planetary ball mill. The ball milling time is 24 hours, the speed is 400 r / min, and the planetary ball mill is set to run for 1 hour and stop for 15 minutes.
[0044] Step 2: Place the ball-milled powder in a drying oven and dry it at 75°C. Pre-sinter the dried powder in a high-temperature box furnace at a pre-sintering temperature of 1200°C, a heating rate of 5°C / min, and a holding time of 3h to obtain Mg2SiO4 powder.
[0045] Step 3: Prepare SrTiO3 powder (purity of 99.9%), a certain mass of PVA and stearic acid, and Mg2SiO4 powder obtained after pre-calcination and place them in a ball mill. Use anhydrous ethanol as the ball milling medium. The ball milling time is 8 hours and the ball mill speed is 400r / min. The amount of SrTiO3 powder added x (wt.%) is controlled to be 2%, 4%, 6%, and 8% of the Mg2SiO4 powder respectively, and the amount of PVA added is 3.5wt.% of the total mass of SrTiO3 powder and Mg2SiO4 powder, and the amount of stearic acid added is 2.5wt.% of the total mass of SrTiO3 powder and Mg2SiO4 powder.
[0046] Step 4: The dried mixed powder is sieved through 40-mesh, 60-mesh and 80-mesh sieves respectively. The remaining powder after each sieving does not exceed 10%, and is added to the sieved powder for the next sieving.
[0047] Step 5: The granulated powder is pressed into a sample using a manual press, with a pressing pressure of 4 MPa and a holding time of 5 min. Sintering is performed in a high temperature box, with a heating rate of 5 °C / min, a sintering temperature of 1340 °C, a holding time of 3 h, and then cooled to room temperature with the furnace.
[0048] Since different SrTiO3 doping amounts have a great influence on the performance of ceramic materials, the microwave performance test was carried out on a sample with a doping amount of 4wt%, and its dielectric constant was 6.99, the quality factor was 28,886GHz, the resonant frequency temperature coefficient was -32.5ppm / ℃, and the thermal expansion coefficient was 9.67×10 -6 K -1 .
[0049] The dielectric properties of the ceramic material obtained in this comparative example were tested, and the test results are shown in Table 1.
[0050] Table 1 Dielectric properties of ceramic materials prepared using Comparative Example 1
[0051]
[0052] Example 1
[0053] Step 1: Calculate and weigh the corresponding mass of MgO and SiO2 raw material powders (purity of 99.99%) according to the chemical formula ratio. Place the accurately weighed powders in a ball mill for ball milling. During the wet mixing ball milling process, anhydrous ethanol is used as the ball milling medium. ZrO2 grinding balls with diameters of 8 mm and 4 mm are added. The total mass ratio of large and small grinding balls to powder is 2:1:1. Stir thoroughly with a glass rod to mix them evenly. Place them in a planetary ball mill. The ball milling time is 24 hours, the speed is 400 r / min, and the planetary ball mill is set to run for 1 hour and stop for 15 minutes.
[0054] Step 2: Place the ball-milled powder in a drying oven and dry it at 75°C. Pre-sinter the dried powder in a high-temperature box furnace at a pre-sintering temperature of 1200°C, a heating rate of 5°C / min, and a holding time of 3h to obtain Mg2SiO4 powder.
[0055] Step 3: Prepare SrTiO3 powder (purity of 99.9%), a certain mass of PVA and stearic acid, and Mg2SiO4 powder and place them in a ball mill. Use anhydrous ethanol as the ball milling medium. The ball milling time is 8 hours and the ball mill speed is 400r / min. The amount of SrTiO3 powder added x (wt.%) is controlled to be 2%, 4%, 6%, and 8% of the Mg2SiO4 powder respectively, and the amount of PVA added is 3.5wt.% of the total mass of SrTiO3 powder and Mg2SiO4 powder, and the amount of stearic acid added is 2.5wt.% of the total mass of SrTiO3 powder and Mg2SiO4 powder.
[0056] Step 4: The dried mixed powder is sieved through 40-mesh, 60-mesh and 80-mesh sieves respectively. The remaining powder after each sieving does not exceed 10%, and is added to the sieved powder for the next sieving.
[0057] Step 5: The granulated powder is pressed into a sample with a manual press, the pressing pressure is 4MPa, and the holding time is 5min. Sintering is performed in a high temperature box, the heating rate is set to 5℃ / min, the sintering temperature is 1180℃, the holding time is 3h, and the sample is cooled to room temperature with the furnace.
[0058] Since different SrTiO3 doping amounts have a great influence on the performance of ceramic materials, a sample with a doping amount of 4wt% was used for microwave performance testing, and its dielectric constant was 7.16, the quality factor was 67,124GHz, the resonant frequency temperature coefficient was -22.6ppm / ℃, and the thermal expansion coefficient was 10.84×10 -6 K -1 .
[0059] The dielectric properties of the ceramic material obtained in this example were tested, and the test results are shown in Table 2.
[0060] Table 2 Dielectric properties of ceramic materials prepared using Example 1
[0061]
Claims
1. A method for preparing a silicate-based microwave dielectric ceramic, characterized in that: Mg2SiO4 powder and SrTiO3 powder are mixed according to the designed ratio to obtain ceramic mixed powder, and then a binder and a lubricant are added to the ceramic mixed powder, and then ball milling is performed to obtain ball milling material, and the granules obtained by granulating the ball milling material are pressed to obtain green body, and the green body is sintered to obtain silicate-based microwave dielectric ceramics, and the sintering temperature is 1180°C, the insulation time is 3-5h, and the heating rate is 1-5°C / min; The process of obtaining the Mg2SiO4 powder is as follows: mixing MgO powder and SiO2 powder to obtain a mixed powder, wet-mixing the mixed powder and ball-milling the mixed powder to obtain a ball-milled powder, and pre-calcining the ball-milled powder to obtain the Mg2SiO4 powder; During the wet mixing ball milling, anhydrous ethanol is used as the ball milling medium, ZrO2 balls are used as grinding balls, the speed of the wet mixing ball milling is 300-450r / min, and the time of the wet mixing ball milling is 18-24h; During the wet mixing ball milling, the ZrO2 balls are composed of large balls with a diameter of 6-10 mm and small balls with a diameter of 2-6 mm, wherein the mass ratio of the large balls, the small balls and the mixed powder is 3-5:1-2:1-2; The pressing pressure is 2-5 MPa, and the holding time is 3-8 min. The chemical expression of the silicate-based microwave dielectric ceramic is Mg2SiO4- x wt.%SrTiO3, where 2≤ x ≤8.
2. The method for preparing a silicate-based microwave dielectric ceramic according to claim 1, characterized in that: The purity of the MgO powder and SiO2 powder is ≥99.99%; In the mixed powder, the mass ratio of MgO:SiO2 is 2-6:1-5.
3. The method for preparing a silicate-based microwave dielectric ceramic according to claim 1, characterized in that: During the pre-firing, the heating rate is 1-5°C / min, the pre-firing temperature is 1000°C-1300°C, and the pre-firing time is 2-4h.
4. The method for preparing a silicate-based microwave dielectric ceramic according to claim 1, characterized in that: The binder is PVA, and the lubricant is stearic acid, wherein the amount of PVA added is 2wt.%~5wt.% of the mass of the ceramic mixed powder, and the amount of stearic acid added is 1wt.%~5wt.% of the mass of the ceramic mixed powder.
5. The method for preparing a silicate-based microwave dielectric ceramic according to claim 1, characterized in that: During the ball milling, anhydrous ethanol is used as the ball milling medium, the ball-to-material ratio is 5-10:1, the ball milling speed is 300-450 r / min, and the ball milling time is 8-12 h.
6. An application of a silicate-based microwave dielectric ceramic prepared by the preparation method according to claim 1, characterized in that: The silicate-based microwave dielectric ceramic is applied to substrate materials of microwave components.
Citation Information
Patent Citations
Mg2SiO4 dielectric constant microwave ceramic medium and its producing process
CN101429015A
Microwave dielectric ceramic material, preparation method thereof and microwave dielectric ceramic device
CN115959895A